Scientific basis or the need for organizing fixed asset analysis in budgetary organizations based on international standards - Bovoboev Saidmurod (THE INNOVATION ECONOMY, 2026)
This article examines the theoretical and practical aspects of organizing the analysis of fixed assets in budgetary organizations based on international standards. The study was conducted using IPSAS 17 and the national accounting standards of the Republic of Uzbekistan. Using document analysis and comparative analysis methods, differences between national practice and international standards were identified, and ways to improve the transparency of financial reporting and the efficiency of asset utilization were proposed. Based on the results, the necessity of adapting international standards and scientifically grounded recommendations were developed.